2021
DOI: 10.1002/jrs.6258
|View full text |Cite
|
Sign up to set email alerts
|

Detection of structural degradation of porcine bone in different marine environments with Raman spectroscopy combined with chemometrics

Abstract: The investigation of time since exposure and taphonomic alteration of bone in marine environments is crucial in forensic sciences. In this study, we explored the diagenetic changes to juvenile porcine bone in two different environmental marine contexts (submerged and intertidal) and how seasonal variation at time of deposition impacted on the pattern of taphonomic alteration in bone during early stages of exposure, from 6 to 24 weeks. The analysis was conducted using Raman spectroscopy combined with chemometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…They demonstrated that Nile Red staining enables the identification of fluorescent particles and provides a method for fast analysis at a low cost and with low equipment needs. Garagoda Arachchige et al also used Raman spectroscopy in combination with chemometrics to detect the structural degradation of porcine bone in different marine environments . This research is timely since the exposure and taphonomic alterations of bone in environments like marine conditions are a crucial area of investigation for environmental forensics.…”
Section: Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that Nile Red staining enables the identification of fluorescent particles and provides a method for fast analysis at a low cost and with low equipment needs. Garagoda Arachchige et al also used Raman spectroscopy in combination with chemometrics to detect the structural degradation of porcine bone in different marine environments . This research is timely since the exposure and taphonomic alterations of bone in environments like marine conditions are a crucial area of investigation for environmental forensics.…”
Section: Biologymentioning
confidence: 99%
“…Bones were also not misclassified between the control group and the environmental study. SVM analysis was used to classify bone type, exposed environment, and season with >80% accuracy . The researchers also investigated other applications of this method, such as the identification of specific algal markers in aquatic environments, which would be helpful for determining seasonal deposition of bones .…”
Section: Medicinementioning
confidence: 99%
See 1 more Smart Citation